L-carnitine supplementation to gestating gilts alters the IGF axis in porcine embyronic myoblasts - K R Brown; B J Johnson; J C Woodworth; Robert D Goodband; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 2006)
We determined the effects of supplemental L-carnitine on the insulin-like growth factor (IGF) system in porcine embryonic myoblasts (PEM) from gilts. Forty gilts (BW = 303.6 lb) were allotted to 1 of 4 treatments that were arranged in a 2 × 2 factorial, with main effects of L-carnitine (0 or 50 ppm) and day of gestation (55 or 70). All gilts were fed 3.86 lb/day and a top-dress containing either 0 or 50 ppm of L-carnitine, starting on the first day of breeding and continuing through the allotted gestation length. At d 55 or 70 of gestation, fetuses were removed for isolation of PEM from the hind-limb muscles. Real-time quantitative PCR was used to determine growth factor messenger RNA (mRNA) expression in cultured PEM at 72-, 96-, 120-, and 144-h after plating. Flow cytometry was used to analyze percentage of myogenic cells with a myoblast/myotube specific monoclonal antibody 5.1H11, and for determination of cell cycle stage. There was no treatment differences (P>0.10) for the expression of IGF-I, IGF-II, or IGFBP-5 mRNA levels. But PEM isolated from fetuses collected from gilts fed diets with L-carnitine had lower (P = 0.08) IGFBP-3 mRNA levels, compared with levels in the controls. Myoblasts isolated from fetuses from gilts fed diets with added Lcarnitine had greater (P = 0.09; 8.8%) 5.1H11 monoclonal antibody attachment, compared with the controls, after 72 hours in culture (91.8% vs. 87.4%). Although not significant (P = 0.31), the total number of PEM in the S phase of the cell cycle was 4.7% greater in PEM collected from fetuses obtained from gilts fed diets with L-carnitine, compared with numbers from the control-fed gilts (37.5% vs. 34.2%). These data suggest that L-carnitine influences the IGF system, stage of the cell cycle, and recognition of muscle development, resulting in enhanced proliferation and delayed differentiation of PEM.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Insulin-like growth factor; Insulin-like growth factor binding proteins; L-carnitine; Messenger RNA; Myoblasts; Pigs; Swine